Partial organic substitution for chemical fertilizer reduces N2O emissions but increases the risk of N loss through nitrification in Tibetan farmland - Huang, Xiaofang; Yu, Chengqun; Sun, Wei; Shi, Peili; Wu, Junxi; Yu, Jialuo; Wang, Jiabao; Mu, Tao (Scientific reports, 2025)
The combination of organic fertilizers (OFs) and chemical fertilizers (CF) is a promising agricultural management strategy to improve soil fertility while mitigating N 2 O emissions in croplands. However, there is still lacking of in-depth understanding of the effects of different OF and CF blends on N 2 O emissions and the underlying drivers. To this end, we conducted a short-term soil incubation to address the influences of partial OF substitutions for CF, i.e., 40% substitution of compost (CP), Yak dung (YD), Qingke straw (QS), and sheep dung (SD) on the processes of nitrification and denitrification in sandy loam soils in the Lhasa Valley. We found that CP, QS, and SD reduced cumulative N 2 O emissions by 53.43%, 25.96% and 16.64%, respectively compared to pure chemical fertilizer (N), except YD caused a significant higher in total N 2 O emissions. Fertilization treatments primarily regulate potential N 2 O emissions by affecting denitrification processes. While ammonia-oxidizing archaea (AOA amoA ) could be the main driver of nitrification, and nirS abundance explained most of the cumulative N 2 O emissions. In addition, NO 3 − –N tends to accumulate in the farmland soils, indicating an increase in the risk of leaching and nutrient loss. Overall, soil N 2 O emission reduction was favored by applying partial organic fertilizer substitution especially after through compost. Co-composting of animal manure and crop residue has more impressive potential for mitigating farmland N 2 O emissions.